2011
DOI: 10.1124/jpet.111.180828
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase Pathway Is Involved in Aortic Contraction Induced by A3 Adenosine Receptor in Mice

Abstract: The NADPH oxidase (Nox) subunits 1, 2 (gp91 phox), and 4 are the major sources for reactive oxygen species (ROS) in vascular tissues. In conditions such as ischemia-reperfusion and hypoxia, both ROS and adenosine are released, suggesting a possible interaction. Our aim in this study was to examine the A 3 adenosine receptor (A 3 AR)-induced vascular effects and its relation to ROS and Nox1, 2, and 4 using aortic tissues from wild-type (WT) andϪ5 M) induced contraction of the aorta from WT but not from A 3 KO m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 36 publications
(48 reference statements)
1
42
0
Order By: Relevance
“…In contrast, Nox2 inhibition or ROS scavenging blunted the adenosine-induced vasodilation in cerebral arteries [35] and coronary circulation [37], both of which suggest that adenosine is capable of generating ROS in these vasculatures. Consistent with our previous findings in the coronary circulation but in contrast to those in other vascular beds [33,34,37], Nox2 inhibition or ROS scavenging significantly attenuated the adenosine-mediated increase in coronary flow, suggesting that adenosine-mediated coronary vasodilation is in part attributed to Nox2-derived ROS. This heterogeneity might be due to vasoconstrictor ROS vs. vasodilator ROS [29,31] generated from different vascular beds (coronary vs. renal artery) [34,37].…”
Section: Adenosine-induced Increase In Coronary Flow Is Mediated In Psupporting
confidence: 91%
See 4 more Smart Citations
“…In contrast, Nox2 inhibition or ROS scavenging blunted the adenosine-induced vasodilation in cerebral arteries [35] and coronary circulation [37], both of which suggest that adenosine is capable of generating ROS in these vasculatures. Consistent with our previous findings in the coronary circulation but in contrast to those in other vascular beds [33,34,37], Nox2 inhibition or ROS scavenging significantly attenuated the adenosine-mediated increase in coronary flow, suggesting that adenosine-mediated coronary vasodilation is in part attributed to Nox2-derived ROS. This heterogeneity might be due to vasoconstrictor ROS vs. vasodilator ROS [29,31] generated from different vascular beds (coronary vs. renal artery) [34,37].…”
Section: Adenosine-induced Increase In Coronary Flow Is Mediated In Psupporting
confidence: 91%
“…Given the fact that Nox has been suggested to be the major source of ROS in coronary vasculature [32,52], it is not clear whether this leads to the generation of ROS by adenosine. We recently found that activation of A 3 AR enhances Nox2-derived ROS contributing to vascular contraction in mouse aorta [33], suggesting a role of A 3 AR in relation to ROS production. In contrast, in the coronary circulation, we have already excluded the involvement of A 1 and A 3 ARs in increased flow that is coupled to the activation of Nox2 [37].…”
Section: Adenosine-induced Increase In Coronary Flow Is Mediated In Pmentioning
confidence: 96%
See 3 more Smart Citations